USIM's Handbook On Academic Writing - Universiti Sains Islam Malaysia (Universiti Sains Islam Malaysia, 2022)
Ethnography has, as its central principle, belief that the context in which a behaviour occurs has a significant impact on that behaviour. This study is based on a four-week ethnographic study of a discourse community- the first and second year students of Universiti Sains Islam Malaysia.